2005
DOI: 10.1097/01.brs.0000168546.17788.49
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Considerations for the Pedicle Screw Placement in the First Cervical Vertebra

Abstract: The heights of the C1 pedicle, the posterior arch under the groove and the posterior lamina at the screw entry point are the major determinants for the possibility of placing pedicle screws in C1 of a given patient. This study indicates that it is feasible to place a 3.5-mm pedicle screw safely in C1 in most patients, and the lateral mass of C2 is a reliable anatomic landmark that can be easily identified to help the surgeon determine the optimal screw entry portal conveniently during surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 10 publications
4
87
0
2
Order By: Relevance
“…However, little epidemiologic evidence for this exists. 31,55 A link between PP and head pain was observed by Wight et al 31 who noted a significant overrepresentation of the ring in chiropractic patients presenting with head pain without aura (ie, visual or auditory disturbances). Surgical excision of the PP appears to alleviate the symptoms of headache, vertigo, and basilar insufficiency.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, little epidemiologic evidence for this exists. 31,55 A link between PP and head pain was observed by Wight et al 31 who noted a significant overrepresentation of the ring in chiropractic patients presenting with head pain without aura (ie, visual or auditory disturbances). Surgical excision of the PP appears to alleviate the symptoms of headache, vertigo, and basilar insufficiency.…”
Section: Discussionmentioning
confidence: 93%
“…Because putting a C1LMS in the classical entry point at the junction of the posterior arch and the lateral mass 10,54 causes significant bleeding from the epidural plexus and can possibly cause irritation to the C2 nerve root resulting in occipital neuralgia, some surgeons recommend placing the screw higher, starting in the posterior aspect of the posterior arch. 55 The purported benefits include longer bony purchase, increased rigidity, less C2 ganglion manipulation and postoperative neuralgia, and less intraoperative blood loss due to less disruption of the perineural venous plexus. 9,11,56 The broad posterior arch of the atlas is the best location for this modified screw placement.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, multiple studies have investigated the anatomy and feasibility of C1 pedicle screw placement [10][11][12][18][19][20][21][22]. Most investigations insisted that the mediolateral width at the isthmus of the C1 pedicle was large enough to insert a 3.5-mm diameter screw [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…However, controversy over the transverse direction of the C1 pedicle screw has existed for a long time [10][11][12]. Tan et al [10] suggested that the screw trajectory should be perpendicular to the coronal plane, whereas Ma et al [11] recommended medial inclination by about 10°, because complications such as neurovascular injury could arise from the lateral mass screw technique [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The same technique was employed in 2014 by Ma et al for IAAD. 143 However, in 2010, Wu et al could access the corresponding field with the tubular approach. 144 The entry incision was high cervical, medical to sternocleidomastoid.…”
Section: History Of Surgical Intervention In Iaadmentioning
confidence: 99%